Methodologies for the analysis of expression and quantification of proteins conferred in tissues of GM crops - Verdugo-Fuentes, Abel Alberto; Castro Espinoza, Luciano; Gutiérrez-Coronado, Marco A.; Martínez-Carrillo, José Luis (Revista Mexicana de Ciencias Agrícolas, 2019)
The Cry toxins of Bacillus thuringiensis (Bt) are used as bioinsecticides in agriculture. Reliable methods are needed to analyze the characteristics that are conferred to genetically modified (GM) plants during their development, before commercialization. The objective of the work was to standardize methodologies for the analysis of the expression of genes and proteins conferred to GM cotton during its different phenological stages in the field. As the main practical application of the study, the standardized methodologies can be used in the characterization of GM crops that are developed and for which it is necessary to carry out their risk analysis. To do this, samples of plant tissue were processed in different phenological stages obtained from GM cotton commercial farms in the Yaqui Valley. In the different tissues, gene and protein expression was quantified by RTq-PCR and Elisa analysis, respectively. The results obtained show variation in the expression of the genes conferred throughout the development of the same variety and between the different sites where the crops were located. The highest levels of expression were identified, as expected, in the early stages of the culture (average values of 8.5 μg g-1 for Cry1Ac and 63.1 μg g-1 for Cry2Ab) compared with that observed in late or mature stages (mean values 0.05 and 0.3 μg g-1 for Cry1Ac and Cry2Ab, respectively). Therefore, it is concluded that the RTq-PCR and ELISA techniques are suitable to evaluate the spatial and temporal expression of genes that are conferred to GM plants, information required to characterize the exposure to the hazard and to perform the risk analysis.
Keywords: gene expression analysis; GM crops; protein expression analysis